197k views
3 votes
For
f(x) = 4x + 1 and
g(x) = x^(2) -5, find
(f - g)(x)

A.
-x^(2) + 4x + 6
B.
4x^(2) - 19
C.
-x^(2) +4x - 4
D.
x^(2) - 4x -6

User Augustomen
by
5.4k points

2 Answers

1 vote

Answer:

Choice A is correct anser.

Explanation:

From question statement,we observe that

Two functions are given. We have to find their difference.

f(x) = 4x+1 and g(x) = x²-5

(f-g)(x) = ?

(f-g)(x) = f(x) - g(x)

(f-g)(x) = (4x+1)-(x²-5)

(f-g)(x) = 4x+1-x²+5

Adding like terms,we get

(f-g)(x) = 4x-x²+6

(f-g)(x) = -x²+4x+6 which is the solution.

5 votes

Answer:


-x^2+4x+6

Explanation:

f(x)= 4x+1

g(x)= x^2-5

We need to find (f-g)(x)


(f-g)(x)= f(x) - g(x)

We need to plug in f(x) and g(x)


(f-g)(x)= f(x) - g(x)=4x+1 -(x^2-5)

Now simplify it


f(x) - g(x)=4x+1 -x^2+5

Combine like terms


f(x) - g(x)=4x -x^2+6

Final answer is


-x^2+4x+6

User Gaurang
by
5.7k points